Growth of single crystals of methylammonium lead mixedhalide perovskites - Nguyen-Tran, Thuat; An, Mai Ngoc; Luong, Trang Thu; Nguyen, Hung Huy; Truong, Tu Thanh (Communications in Physics, 2018)
We report the growth and characterization of different bulk single crystals of organo lead mixed halide perovskites CH3NH3PbI3−xBrx by two different crystal growth approaches: (i)anti-solvent diffusion, and (ii) inverse temperature crystallization. In order to control the size and the shape of crystals, we have investigated different experimental growth parameters such as temperature and precursor concentration. The morphology of obtained crystals was observed by optical microscope, whereas their intrinsic crystalline properties were characterized by single crystal as well as powder X-ray diffraction. The results illustrated that the growth and crystalline structure of mixed halide perovskites CH3NH3PbI3−xBrx could be easily tuned.